RESPON SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA PADA MATERI GEOMETRI BERDASARKAN TAKSONOMI SOLO DITINJAU DARI TINGKAT METAKOGNISI SISWA KELAS X SMA NEGERI 1 CEPU - Salistiyani, Salistiyani; Usodo, Budi; Pramudya, Ikrar (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: This research aimed to describe the response of the 10th graders of SMA 1 Cepu to solve the mathematic problem in geometric material based on SOLO taxonomy in the students with high, medium and low metacognitive ability. This study was a qualitative research with nine students in the 10th graders of SMA Negeri 1 Cepu: three students with high, three with medium and three with low metacognition abilities. The subject of research was selected using purposive sampling technique. Techniques of collecting data used were written test and interview. Data validation was carried out using time triangulation. Technique of analyzing data used included data collection, data reduction, data display and verification. The result of research showed that the studentsâ response to solve mathematic problem based on SOLO taxonomy (1) The response of students with high metacognitive level, students could solve the unistructural, multistructural, and relational problem but they couldnât solve the extended abstract problem, from the response given, it could be concluded that the students with high metacognition occupied the relational level (2) The response of students with medium metacognition, the students could solve the unistructural problem but they couldnât solve the multistructural, relational and extended abstract problem. Based on the response given, it could be concluded that the students with medium metacognition still occupied unistructural level. (3) The response of students with low metacognition, students could solve unistructural but there was exist the students who couldnât answer unistructural problem because they did not have any aspect to solve the problem, in addition students coldnât also to solve multistructural, relational, and extended abstract problem. Based on the response given, it could be concluded that the students in low metacognition category occupied prestructural and unistructural level.Key words: studentsâ response, SOLO taxonomy, metacognitive ability